ナンキョク ショウワ キチ ノ ピロティ ケイシキ タテモノ シュウヘン ノ フキダマリ セイジョウ ニ カンスル フウドウ モケイ ジッケン - 苫米地, 司; トマベチ, ツカサ; 遠藤, 明久; エンドウ, アキヒサ; Tomabechi, Tsukasa; Endo, Akihisa (1985)
P(論文) 模型雪に活性白土を使用した風洞模型実験(縮尺100分の1)で, 南極昭和基地で調査された高床式建物後方の吹きだまり形状の再現の可能性を検討した。その結果, 風洞内風速5.0m/s, 風洞の運転時間2.5時間で現地の吹きだまり形状を再現することができた。今後, 同様の実験方法で, 建物周辺の吹きだまりを少なくするための建物形状の検討が可能であることを示した。 To study snowdrift formation behind elevated buildings, wind-tunnel experiments were carried out, using activated clay particles to simulate snow, on a 1/100 scale model of the observation hut at Syowa Station. The similitude of snowdrift for the model and the actual prototype was obtained precisely when the tunnel wind-speed and the wind duration were 5.0m/s and 2.5 hours, respectively. This modeling technique using activated clay particles is proved to be useful for further studies on the most appropriate shape and dimensions of elevated buildings to prevent snowdrift. departmental bulletin paper